Contributions of burning incense on indoor air pollution levels and on the health status of patients with chronic obstructive pulmonary disease - Guo,Su-Er; Chi,Miao-Ching; Lin,Chieh-Mo; Yang,Tsung-Ming (PeerJ, 2020)
Background Among Buddhist or Taoist Taiwanese residents, burning incense is a common source of indoor particulate matter (PM), including PM10 and PM2.5, and can adversely affect the health status of patients with chronic obstructive pulmonary diseases (COPD). However, few studies have focused on the effects of intermittent burning of incense on PM concentration levels and the health status of patients with COPD. This correlational cohort study aimed to investigate the association between burning incense exposure duration, indoor air pollution levels, and lung function in patients with COPD in Taiwan. Methods We assessed 18 outpatients at seven time points with moderate-to-severe COPD using the COPD Assessment Test (CAT), and lung function tests. PM level changes were assessed at seven intervals using generalized estimating equations. Results Participants were primarily male (84%), with a mean age of 72.1 (standard deviation (SD)  ± 9.3) years, and with a mean COPD duration of 3.7 (SD  ± 3.1) years. Both PM10 and PM2.5 levels were the same as the background levels 1 h after incense burning. Burning incense may not influence lung function or symptom severity in patients with COPD in a short-time period. Air quality returned to baseline levels 1 h after burning incense. Conclusion Patients with COPD should avoid staying in rooms where incense is burnt, for up to 1 h. The small sample size and short study period may have influenced our results. Future longitudinal studies with larger sample sizes and long-term follow-ups are recommended.
Keywords: Burning incense; Chronic lung disease; Indoor particulate matter; Lung function